The Concept of Humanist Education: A Qur'anic Perspective - Wibowo, Yusuf Rendi; Salfadilah, Fatonah; Amanabella, Maulina; Malahati, Fildza; Atin, Sri (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2024)
Human beings possess legal rights, preferences, and philanthropic endeavors, which provide the foundation of the concept of humanizing education under humanist learning theory. Nevertheless, numerous educators in Indonesia continue to eschew a humanist approach in their pedagogy, thereby constraining the development of students' capabilities through authoritarian regulations. This study highlights these issues and emphasizes the necessity of humanist education in fostering constructive interactions between educators and learners. The humanist method prioritizes teacher empathy, fostering an effective and inclusive educational environment. The article examines the notion of humanism in Islam by analyzing Qur'anic passages. This research is descriptive qualitative, employing a philosophical method and maudhu'i interpretation. The findings indicated that the Qur'an encompasses humanist principles that advocate for a comprehensive approach to education. This research enhances the comprehension of humanistic education within Islam by demonstrating the alignment of humanistic values in the Qur'an with the tenets of Islamic education. The recognition of moral responsibility, commitment to lifelong learning, and reverence for human dignity constitute the fundamental principles for a comprehensive and development-focused education of the entire individual, aligned with Islamic teachings.